Treatment of Cirrhosis-Associated Hyponatremia with Midodrine and Octreotide - Patel, Sharad; Nguyen, Dai-Scott; Rastogi, Anjay; Nguyen, Minh-Kevin; Nguyen, Minhtri K. (Frontiers in Medicine, 2017)
Background Hyponatremia in the setting of cirrhosis is a common electrolyte disorder with few therapeutic options. The free water retention is due to non-osmotic vasopressin secretion resulting from the cirrhosis-associated splanchnic vasodilatation. Therefore, vasoconstrictive therapy may correct this electrolyte abnormality. The aim of this study was to assess the efficacy of midodrine and octreotide as a therapeutic approach to increasing urinary electrolyte-free water clearance (EFWC) in the correction of cirrhosis-associated hyponatremia. Methods This observational study consisted of 10 patients with cirrhosis-associated hyponatremia. Hypovolemia was ruled out as the cause of the hyponatremia with a 48-h albumin challenge (25 g IV q6 h). Patients whose hyponatremia failed to improve with albumin challenge were started on midodrine and octreotide at 10 mg po tid and 100 μg sq tid, respectively, with rapid up-titration as tolerated to respective maximal doses of 15 mg tid and 200 μg tid within the first 24 h. We assessed urinary EFWC and serum sodium concentration before and 72 h after treatment. Results Pretreatment serum sodium levels ranged from 119 to 133 mmol/L. The mean pretreatment serum sodium concentration ± SEM was 124 mmol/L ± 1.6 vs 130 mmol/L ± 1.5 posttreatment (p = 0.00001). The mean pretreatment urinary EFWC ± SEM was 0.33 L ± 0.07 vs 0.82 L ± 0.11 posttreatment (p = 0.0003). Conclusion Our data show a statistically significant increase in serum sodium concentration and urinary EFWC with the use of midodrine and octreotide in the treatment of cirrhosis-associated hyponatremia.